Produção, caracterização microestrutural e avaliação de propriedades de compressão e dureza de ligas Ti-Si-B com adição de Nb visando o desenvolvimento de biomateriais - Ferreira, Robson Leopoldino (2019)
Titanium has been widely used as a biomaterial, especially in orthopedic and dental applications, as it has an attractive ratio of mechanical strength/specific mass, corrosion resistance and good biocompatibility characteristics. Recent studies have observed that Ti-Si-B alloys formed by Ti+Ti6Si2B phases have good bone integration and biocompatibility characteristics, which are superior to those presented by pure titanium and Ti-6Al-4V alloy. Because they do not have aluminum in their composition, these alloys have lower potential for toxicity (local and systemic) for implantable device applications. However, information about the mechanical properties of Ti-Si-B alloys formed by Ti6Si2B is still limited in the literature. As the Ti6Si2B phase has a small single phase region, the addition of small amounts other elements such as Mo, Nb, Ta and Zr has been considered in Ti-Si-B alloys, so as not to compromise their stability. Thus, this work evaluates the effect of 2%-atomic addition of Nb on Ti6Si2B phase stability and on the mechanical compression properties of Ti-Si-B alloys. Elemental powders were used for the preparation of Ti-2Si-1B, Ti-6Si-3B, Ti-10Si-5B, Ti-2Nb-2Si-1B, Ti-2Nb-6Si-3B and Ti-2Nb-10Si-5B alloys (%-atomic) by high energy milling (for 180 minutes) and subsequent spark plasma sintering (SPS) (1150°C, 15 min, 20 MPa). To minimize the occurrence of excessive cold welding mechanisms, the addition of 5% vegetable paraffin mass in relation to the total mass of powders to be processed by high energy grinding was used. The ground samples were characterized by laser diffraction, thermal analysis, X-ray diffraction (XRD) and scanning electron microscopy (SEM) techniques. After sintering, the samples were evaluated by XRD, SEM, dispersive energy spectrometry (EDS), compression tests and Vickers microhardness. Vegetable paraffin, Ti-α and Si were identified in the X-ray diffractograms of Ti-Nb-Si-B powders prepared in this work. The addition of vegetable paraffin was efficient to minimize excessive adhesion of ductile powder particles during grinding. Laser diffraction particle size analysis of the ground materials indicated that the values ​​of D10, D50 and D90 ranged from 43,8 to 47,8μm; 65,7-85,5μm and 110,9-144,5μm for Ti-Si-B powder mixtures and between 43,3-52,1μm; 67,9-88,9μm and 117,0-152,1μm for Ti-Nb-Si-B evaluated in this study, indicating that the samples richest in Si and B presented higher amounts of fine particles due to the higher tendency of occurrence of fracture mechanisms during grinding. TG curves of milled powders indicated the presence of endothermic peaks at temperatures between 200 and 300°C, which is related to the decomposition of vegetable paraffin during heating. Regardless of the addition of Nb, the XRD, SEM and EDS analyzes of the sintered samples indicated the presence of the Ti6Si2B phase, in addition to other phases such as Ti5Si3 and TiB, which is related to the short sintering time adopted (15 min), necessary for the occurrence of atomic diffusion. In these samples, regions with iron and carbon in their composition were also noted, coming from the milling vessel/spheres and the vegetable paraffin, respectively. As expected, the intensity of the ternary phase peaks increased in richer Si and B alloys. The Ti-Si-B alloy compression tests indicated that the mean values ​​of modulus of elasticity, yield stress, strength limit, stress rupture, total deformation, resilience and material toughness ranged from 21,9 to 24,4 GPa; 1068-1143 MPa; 1351-1641 MPa; 1234-1566 MPa; 1,18-2,05 mm; 35,5-39,2 J/m3 and 126,5-271,9 J/m3, respectively. In Ti-Nb-Si-B alloys, these values ​​were between 18,2-2,5 GPa; 800-1061 MPa; 957-1429 MPa; 869-1371 MPa; 1,02-2,12 mm; 29,6-37,3 J/m3 and 89,3-246,1 J/m3, respectively, indicating that the addition of Nb reduced these values. Ti-Si-B alloys showed average Vickers microhardness values ​​between 355,9 to 401,9 HV, while Ti-Nb-Si-B alloys ranged from 324,9 to 390,4 HV. As expected, Vickers mechanical compressive strength and microhardness values ​​were increased for Si and B rich alloys due to the higher amount of Ti6Si2B present in the microstructure of the alloys.